Promoting International Energy Security Volume 3, Sea-Lanes to Asia - Henry, Ryan (RAND Corporation, 2012)
The sea-lanes that supply Asia's energy needs are unquestionably vulnerable, but alternatives to the U.S. Navy's traditional role in protecting them have become desirable. One approach would be employ multiple U.S. military and government elements; a second would promote the capabilities of and cooperation among nations in the region.